Living Complex. From Zombie City to the New Communal. - Maak, Niklas (Hirmer, 2015)
Die Städte weltweit veröden, die Massen ziehen in die Vorstädte. Die Bauindustrie boomt und fertigt immer die gleichen Behausungen. Doch die Gesellschaft wandelt sich. Welche Wohnformen brauchen wir heute für unsere vielfältigen Lebensentwürfe? Der Autor präsentiert Beispiele weltweit für ein neues Wohnen jenseits von Apartmentriegel und Einfamilienhaus und zeigt, dass das Bauen, das Wohnen und die Stadt neu gedacht werden müssen - über die klassischen Kategorien von privat und öffentlich hinaus.

Niklos Maak provocatively argues that the construction industry, the commercialization of housing, and a number of outdated policies have prevented us from rethinking how we live in the city. Yet many of our current crises - from the mortgage crisis to global warming - are closely linked to problematic forms of accommodation in our cites. And the problem will only get worse: over the next 20 years, influx into cities is expected to create the need for one billion new housing units. Fortunately, Maak shows, there are practicable solutions. In Europe, Japan, and the US, he explores promising new forms of housing and collective living. Cities should be reflections of their inhabitants, not forces to be contended with.
Keywords: Wohnungswesen; Wohnungsbau; Architektur; Bauplanung; Städtebau; Gebäude; Wohnumfeld; Wohnform; Stadtstruktur